2007
DOI: 10.1523/jneurosci.1874-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Signal-Regulating Kinase 1 in Amyloid β Peptide-Induced Cerebral Endothelial Cell Apoptosis

Abstract: A pathological hallmark of Alzheimer's disease is accumulation of amyloid-␤ peptide (A␤) in senile plaques. A␤ has also been implicated in vascular degeneration in cerebral amyloid angiopathy because of its cytotoxic effects on non-neuronal cells, including cerebral endothelial cells (CECs). We explore the role of apoptosis signal-regulating kinase 1 (ASK1) in A␤-induced death in primary cultures of murine CECs. A␤ induced ASK1 dephosphorylation, which could be prevented by selective inhibition of protein phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 52 publications
2
75
0
Order By: Relevance
“…Mouse CECs were prepared as described previously (Hsu et al, 2007). Briefly, the gray matter of fresh mouse brains was homogenized and filtered, and the resulting fraction was then sequentially digested with 4 mg/mL collagenase B for 2 h and 1 mg/mL collagenase/dispase (Roche Molecular Biochemicals, Indianapolis, IN) for 2 h, followed by centrifugation in a 40% Percoll solution.…”
Section: Mouse Cec Primary Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Mouse CECs were prepared as described previously (Hsu et al, 2007). Briefly, the gray matter of fresh mouse brains was homogenized and filtered, and the resulting fraction was then sequentially digested with 4 mg/mL collagenase B for 2 h and 1 mg/mL collagenase/dispase (Roche Molecular Biochemicals, Indianapolis, IN) for 2 h, followed by centrifugation in a 40% Percoll solution.…”
Section: Mouse Cec Primary Culturementioning
confidence: 99%
“…Cheng et al (2003) demonstrated that ischemia-induced apoptosis of CECs was mediated by increased expression of p53 and activation of caspase-3 signaling. Deposition of b-amyloid (Ab) also induced CEC death via caspase-8/reactive oxygen species (ROS)/apoptosis signal-regulating kinase 1 (ASK)1-dependent apoptosis (Hsu et al, 2007;Xu et al, 2001). Therefore, protection of the BBB from apoptosis may be a beneficial therapeutic strategy for neuronal functions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ASK1 plays pivotal roles in a wide variety of cellular responses, which include, but are not limited to, apoptosis (30,31). Dysregulation of the ASK1 signaling pathway is closely linked to various diseases, such as cancer, cardiovascular diseases, diabetes, and neurodegenerative diseases including polyglutamine-induced neurodegeneration and Parkinson disease (29,(32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%
“…Upon TNFα treatment the AIP1/PP2A complex was found to interact with and dephophorylate ASK1 at Ser967, leading to the dissociation of its inhibitor 14-3-3 and ASK1 activation [49]. Furthermore, Aβ was found to induce ASK1 Ser967 dephosphorylation and its dissociation from the 14-3-3 protein leading to p38 activation, and induction of the pro-apoptopic BCl-2 family member, Bax [50]. Selective inhibition of PP2A prevented the activation of this signaling cascade linking ASK1 Ser967 phosphorylation status to Aβ-induced toxicity.…”
Section: Modulation Of Ask1 Activity By Postranslational Modificationmentioning
confidence: 99%
“…These data strongly suggest that ASK1 could play a significant role in the pathogenesis of AD by mediating ROS and/or Aβ induced neuronal cell death via the MKK6/JNK/p38 pathway. In addition, Aβ was not only shown to cause neuron-specific toxicity, but also demonstrated to cause vascular degeneration in cerebral amyloid angiopathy; Hsu and coworkers employed primary murine cerebral endothelial cells (CEC) to investigate the mode of cell death mediated by Aβ in ASK1 transfected CECs [50]. Aβ exposure was observed to result in an induction of the ASK1-MKK3/6-p38-p53 signaling machinery and increased levels of the pro-apoptotic protein Bax resulting in CEC programmed cell death.…”
Section: Ask1 In Alzheimer's Diseasementioning
confidence: 99%